+0

0
197
5

Let x and y be real numbers whose absolute values are different and that satisfy \begin{align*} x^3 &= 20x + 7y \\ y^3 &= 7x + 20y \end{align*} Find xy.$$$\cfrac{1}{1 + \cfrac{1}{2 + \cfrac{1}{1 + \cfrac{1}{2 + \dotsb}}}}$$$1.

$$a^3 + \dfrac{1}{a^3} if a+\dfrac{1}{a} = 6$$2.

ANNNNNNDDDDDD!

\begin{align*} x^3 &= 20x + 7y \\ y^3 &= 7x + 20y \end{align*}Find $xy$

Guest Jun 8, 2017
Sort:

#1
0

Ignore that text at the top :)

Guest Jun 8, 2017
#4
+421
0

But why did you even put it?

#2
+79843
+1

a^3  +  1/a^3    if    a + 1/a  = 6

Note:  if  a + 1/a   = 6   then

(a + 1/a)^2  = 36

a^2 + 2 + 1/a^2  = 36

a^2 + 1/a^2  =  34

Factor  a^3  +  1/a^3   as

(a +  1/a) ( a^2 - 1 + 1/a^2 )  =

( a + 1/a) ( [a^2 + 1/a^2] - 1)  =

(6) ( [34] - 1)  =

(6) (33)  =

198

CPhill  Jun 8, 2017
#3
+79843
+1

x^3  = 20x + 7y

y^3  = 7x + 20y

Subtract the two equations

x^3  - y^3  = 13x - 13y

(x-y) (x^2 + xy + y^2)  = 13 (x - y)    divide both sides by ( x - y)

x^2 +  xy + y ^2   =  13  →  x^2 + y^2  =  13 - xy   (1)

x^3 + y^3  =  27x + 27y

(x + y) ( x^2  - xy + y^2)  = 27 (x + y)   divide both sides by (x + y)

x^2 - xy + y^2  =  27  →  x^2 + y^2  =  27 + xy    (2)

Then.....setting (1)  and (2)   equal, we have that

13 - xy  =  27 + xy

2xy  = -14

xy  =  -7

[ Note....other solutions  are possible...for instance  the trivial solution of (x, y) = (0, 0)  produces xy = 0 ]

CPhill  Jun 8, 2017
#5
+6900
+1

$$\because x^3=20x+7y\text{ and }y^3=7x+20y\\ \therefore x^3-y^3=(x-y)(x^2+xy+y^2)=13x-13y\\ x^2+xy+y^2 = 13\\ x^3+y^3 =(x+y)(x^2-xy+y^2)=27(x+y)\\ x^2-xy+y^2=27\\ (x^2+xy+y^2)-(x^2-xy+y^2)=-14\\ xy = -7$$

MaxWong  Jun 9, 2017
edited by MaxWong  Jun 9, 2017

### 9 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details